Gravitation: Sätt att läsa i antropocen - Ahlbäck, Pia (Tidskrift för litteraturvetenskap, 2021)
Gravitation: Modes of Reading in the Anthropocene In this article, I suggest ‘gravitation’ as a new way of reading in and for the anthropocene, which is characterised by environmentally destructive ‘social acceleration’. This reading practice would imply two things: First, that representations of the natural environment take a primary position in relation to the characters in many genres, including those where nature so far has been read as a highly conventional construction. It also involves acknowledging that ultimately, characters are positioned by the physical environment in these genres, as characters, in one way or the other, can never exist unrelated to the environment that encompass and cut through them. These genres I suggest be called ‘gravitating genres’. Second, and in a similar fashion, I suggest the term ‘gravitating reading’ to denote reading of physical books, which in this context becomes a highly preferred medium. This term partly coincides with that of ‘deep reading’ suggested by Mangen, but in addition, it also recognizes the dependency of both the reader and the medium on the natural environment. Together, these two practices amount to, I suggest, nothing less than a mutually sustainable economy of reading.